2017
DOI: 10.1002/2016jd026241
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale modeling of smoke transport from equatorial Southeast Asian Maritime Continent to the Philippines: First comparison of ensemble analysis with in situ observations

Abstract: Atmospheric transport of smoke from equatorial Southeast Asian Maritime Continent (Indonesia, Singapore, and Malaysia) to the Philippines was recently verified by the first‐ever measurement of aerosol composition in the region of the Sulu Sea from a research vessel named Vasco. However, numerical modeling of such transport can have large uncertainties due to the lack of observations for parameterization schemes and for describing fire emission and meteorology in this region. These uncertainties are analyzed he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Sensitivity WRF simulations (plots not shown here) were previously run with three cumulus parameterization schemes, namely, Betts-Miller-Janjic (BMJ) [54,55], Kain-Fritsch (KF) [56] and Grell 3D (G3D) cumulus scheme [57] over the model domain for the same study period. In summary, the BMJ scheme showed the best agreement to CMORPH data, and hence, all WRF-Chem simulations for this episode are run with BMJ, which is consistent with a recent study by Ge et al [58] for the case of September 2011 in the Maritime Continent. Pennelly et al [59] also report that BMJ simulates precipitation with better accuracy than KF and G3D at 30 km grid resolution.…”
Section: Model Setupsupporting
confidence: 90%
“…Sensitivity WRF simulations (plots not shown here) were previously run with three cumulus parameterization schemes, namely, Betts-Miller-Janjic (BMJ) [54,55], Kain-Fritsch (KF) [56] and Grell 3D (G3D) cumulus scheme [57] over the model domain for the same study period. In summary, the BMJ scheme showed the best agreement to CMORPH data, and hence, all WRF-Chem simulations for this episode are run with BMJ, which is consistent with a recent study by Ge et al [58] for the case of September 2011 in the Maritime Continent. Pennelly et al [59] also report that BMJ simulates precipitation with better accuracy than KF and G3D at 30 km grid resolution.…”
Section: Model Setupsupporting
confidence: 90%
“…As transport and vertical distributions of BB smoke are shown to be sensitive to smoke injection height in many aerosol modeling studies (Colarco et al, ; Ge et al, ; J. Wang et al, ), another NAAPS simulation, aiming for possible improvement of the vertical distribution of smoke for the NiCE and FASE cases, is tested using the observed average BB layer height as the smoke injection height (approximately 500 m based on the soundings). The default model smoke injection method is to inject smoke mass into the lowest four model layers, with the fourth layer centered around 300 m above ground.…”
Section: Resultsmentioning
confidence: 99%
“…P. Kumar et al () indicated that the model performance on meteorological fields initialized from the ECMWF data set was superior to that initialized from the NCEP data sets over the Indian region. The effect of different meteorological analysis data sets on volcanic ash dispersion (Mulena et al, ) and biomass burning smoke transport (Ge et al, ) has also been investigated. However, overall effect of the two data sets on simulated ambient pollutant concentrations in addition to meteorological fields over India for a whole year has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%